2016
DOI: 10.1007/s10661-016-5577-8
|View full text |Cite
|
Sign up to set email alerts
|

Multitemporal analysis of forest fragmentation in Hindu Kush Himalaya—a case study from Khangchendzonga Biosphere Reserve, Sikkim, India

Abstract: Forests in the mountains are a treasure trove; harbour a large biodiversity; and provide fodder, firewood, timber and non-timber forest products; all of these are essential for human survival in the highest mountains on earth. The present paper attempts a spatiotemporal assessment of forest fragmentation and changes in land use land cover (LULC) pattern using multitemporal satellite data over a time span of around a decade (2000-2009), within the third highest protected area (PA) in the world. The fragmentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 75 publications
2
14
0
3
Order By: Relevance
“…The forest was the main land cover in the study area. The overall trend shows that the forest area had decreased and the non-forest area had increased in the Rudraprayag district; the overall loss of the forest was 122.35 km 2 from 1976 to 2014.This result agrees with other studies conducted in the Himalayan region of India [51,52]. The general trends of change showed an increase in agriculture, barren land, built-up area, and scrub land.…”
Section: Land-use and Land-cover (Lulc) Changesupporting
confidence: 88%
See 1 more Smart Citation
“…The forest was the main land cover in the study area. The overall trend shows that the forest area had decreased and the non-forest area had increased in the Rudraprayag district; the overall loss of the forest was 122.35 km 2 from 1976 to 2014.This result agrees with other studies conducted in the Himalayan region of India [51,52]. The general trends of change showed an increase in agriculture, barren land, built-up area, and scrub land.…”
Section: Land-use and Land-cover (Lulc) Changesupporting
confidence: 88%
“…The local community depends highly on agricultural activity, which would be further expected with a decline in forest cover. Other studies also found similar causes of forest decline in the Hindu Kush Himalaya (HKH) region [49,[52][53][54]. Although natural drivers could also play a role in land cover change, the scope of this study mainly focused on anthropogenic activities.…”
Section: Land-use and Land-cover (Lulc) Changementioning
confidence: 89%
“…Accuracy Assessment of a classified product is a must and is used as a certification for further use in any information interpretation and further modelling. Accuracy of a classified image is generally determined by comparing certain pixels (a sample) of the classified map with the reference (for which the class is known) pixels (Sharma et al, 2016). The source of reference pixels in this study were the GCPs (Ground Control Points) collected during fieldwork and randomly generated sample points in ERDAS Imagine software.…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…Es un proceso dinámico (6) en el que un área amplia e intacta de bosque es progresivamente subdividida en pequeños parches o fragmentos (8,10) geométricamente alterados y aislados (2,5,6,11) inscritos en otros usos del suelo distintos (12), rodeado por matrices generalmente antrópicas (13), lo que genera la modificación de las condiciones medioambientales y el funcionamiento de los ecosistemas (14), (15), provocando elevada mortalidad de árboles y plantas juveniles (13), caída acelerada de las hojas, alteración en el almacenamiento de carbono, y en otros procesos como la abundancia de algunas especies, en la productiva, formación de detritus, movimiento de agua y nutrientes, la sucesión y la competencias entre otros (16,17). Autores han descrito el proceso de fragmentación en cuatro etapas: i) la perforación, en la cual se crea un agujero o hueco en la cobertura original; ii) la subdivisión, en la cual las áreas de coberturas de la tierra más grandes se dividen en parches más pequeños; iii) la contracción, que es la etapa en la cual se pierde la conectividad entre los parches de cobertura original; y por último, iv) la etapa de desgaste, en la cual los parches originales del paisaje disminuyen gradualmente en tamaño hasta que finalmente desaparecen (18,19).…”
Section: Generalidades De La Fragmentación De Bosquesunclassified
“…Debido a esto, ha emergido como una prioridad de investigación, la comprensión de la dinámica de la fragmentación de bosques y los cambios en las coberturas de la tierra, para entender el desarrollo del pasado como base para la planeación y como guía para la conservación en un futuro (6,30). Esto ha ocasionado que el enfoque en la fragmentación tenga altas prioridades en la agenda local de los gobiernos para la formulación de políticas de protección y planeación de uso del territorio (2) de manera que las políticas dirigidas de modo adecuado pueden transformar las áreas agrícolas a bosques en áreas que formen corredores para la vida silvestres, garantizando la persistencia de especies y evitando que afecte negativamente la biodiversidad (31) (32) .…”
Section: Generalidades De La Fragmentación De Bosquesunclassified